2014
DOI: 10.11118/actaun201159070017
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing consumer behaviour in market vegetables in Yemen

Abstract: AL-GAHAIFI, T. H., SVĚTLÍK, J.: Factors infl uencing consumer behaviour in market vegetables in Yemen. Acta univ. agric. et silvic. Mendel. Brun., 2011, LIX, No. 7, pp. 17-28 The purpose of the research is to understand factors infl uencing consumer behaviour when buying vegetables in Republic of Yemen. Data collection was done by structured questionnaire administered through schools, universities, government offi ces, and markets from 13 provinces in 5 governorates. Random convenience sampling technique w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…The results of the survey is supported by mentions of researchers (such [24,13,14,4,12,25]) who consider vegetarianism as personal decision in connection to the consumer behaviour and lifestyle in global worldwide context.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results of the survey is supported by mentions of researchers (such [24,13,14,4,12,25]) who consider vegetarianism as personal decision in connection to the consumer behaviour and lifestyle in global worldwide context.…”
Section: Discussionsupporting
confidence: 61%
“…Vegetarianism includes specific kinds of vegetarianism, where are defined the specific situation of animal products rejection. All individual kinds of vegetarianism are a long-term approach [4,12]. There are many reasons why people accept vegetarianism.…”
Section: Vegetarianism As Lifestylementioning
confidence: 99%
“…Studies have indicated that food Consumers' buying behavior has been influenced by combination of social, economic, cultural, and psychological factors (Al Gahaifi & Svetlik, 2011;Deshingkar, Kulkarni, Rao, & Rao, 2003;Goyal and Singh, 2007;Intercooperation & Shen, 2010;KPMG, 2005;Kuhar & Juvancic, 2010;Leibtag & Kaufman, 2003). It has been reported that besides exogenous factors like culture, reference group, family, and socioeconomic situations, endogenous factors such as needs and motives, learning, self-concept, personalities, and attitudes affected consumers' buying behavior (Crawford, 1997).…”
Section: Consumers' Behaviormentioning
confidence: 97%
“…While Al-Gahaifi and Světlík (2011) determined that the price, status, and purchase time of fresh fruits and vegetables had a high effect on consumers, they suggested that the exhibition and sorting of these products and the position of the seller had a moderate effect.…”
Section: Literature Reviewmentioning
confidence: 99%